The Impact of Urban Configuration to the Urban Heat Island in East Surabaya - Rivan Aji Wahyu Dyan Syafitri; Adjie Pamungkas; Eko Budi Santoso (IPTEK Journal of Proceedings Series, 2020)
Climate change that occurs due to urbanization has implications for increased intraurban heating, or usually called urban heat island (UHI). East Surabaya has the most potential to experience increased surface temperature. The urban area has different configuration characteristics and became the most fundamental impact of the phenomenon. However, East Surabaya in climate resilience response has not emphasized adaptation based on urban configuration spatially. While changing the shape of the urban that has been built is most difficult to restore and requires expensive costs. The purpose of this study is to find what’s characteristics urban configuration caused UHI significantly. So, it can be a reference to an adaptation to minimize UHI intensity from the best type of urban configuration. This study uses a positivist paradigm. Remote sensing using LiDAR and Landsat imagery became the main source of this research. With geographic information system (GIS), UHI in the urban and suburban areas of East Surabaya has a temperature difference of around 1,590C. Characteristics of urban configuration are in classifications 2 to 7. Classification 2 is the central area of activity, while classification 7 is a sub-urban area. Urban Configuration have an impact to the UHI intensity. Classification 3 has the biggest effect on UHI.